Microbial Bioconversion of Dairy Wastewater in Packed Bed Biofilm Reactor into Liquid Biofertilizer. Issue 3 (2nd May 2022) - Gogoi, Mandakini; Banerjee, Somok; Pati, Swatilekha; Ray Chaudhuri, Shaon
Abstract: Dairy industries are highly polluting, energy and fresh water consuming installations. The present study aims to make dairy effluent treatment plant operation less time consuming with minimal energy consumption while generating a value added product. Analysis of the temporal and spatial variation in performance of a biofilm based plug flow reactor involved in the biotransformation of Dairy Waste Water (DWW) revealed ammonia (57.68 mg L –1 ) rich liquid biofertilizer production within 4 h, with associated reduction of nitrate (70.77%), phosphate (36.44%), protein (62.87%), Biological Oxygen Demand (BOD) (26.38%) and Chemical Oxygen Demand (COD) (39.59%). The process was 4 times faster than the fastest existing process reported till date. The consortium showed a striking reduction in its doubling time from 78 min 56 sec (in suspension culture) to 17 min 10 sec (as biofilm) upon immobilization. It could produce 734.60 mg ammonia per kg of immobilization matrix from DWW. Metagenomic analysis revealed the robustness of the biofilm based biotreatment system. The novelty of this study is the innovative approach of rapid conversion of the waste from dairy industry into a value added product using microbes from geosphere in an energy efficient manner which would make dairy effluent treatment plant operation self-sustainable and eco-protective.